2021
DOI: 10.1177/21501351211027478
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reimplantation Procedure in Anomalous Aortic Origin of the Right Coronary Artery: Long-Term Single Center Outcomes

Abstract: Background: Anomalous aortic origin of the right coronary artery is known to be a cause of sudden cardiac death in athletes. There are no specific guidelines concerning treatment strategy in the literature. The aim of this study is to describe and report our experience of direct reimplantation technique in the treatment of this anomaly. Methods: This was a retrospective single center study of 30 patients who underwent surgery in the congenital heart disease unit of Louis Pradel Heart and Lung Hospital between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Reimplantation is technically simple, and the lesion is easily approachable, even if a stenotic lesion in RCA occurs in the future. Previous cases also showed that it might enable surgeons to avoid aortotomy [ 2 , 4 ]. Although, depending on the diameter of the RCA in early childhood, reimplantation could be difficult in principle, it should be considered as an option for adolescent cases with AAORCA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reimplantation is technically simple, and the lesion is easily approachable, even if a stenotic lesion in RCA occurs in the future. Previous cases also showed that it might enable surgeons to avoid aortotomy [ 2 , 4 ]. Although, depending on the diameter of the RCA in early childhood, reimplantation could be difficult in principle, it should be considered as an option for adolescent cases with AAORCA.…”
Section: Discussionmentioning
confidence: 99%
“…Although, depending on the diameter of the RCA in early childhood, reimplantation could be difficult in principle, it should be considered as an option for adolescent cases with AAORCA. Previous studies that reported on more than 10 cases [ 1 , 2 ] suggested that anastomosis could be performed if the proximal part of the RCA had a diameter of 3.5 mm because a 3.5 mm puncher was often used to create neo-ostium in the ascending aorta.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations